Potential And Marine Tourism Development Strategy In The District Teluk Meranti Bono Pelalawan Province Riau - Hakullah Akbar; Hamdi Hamid; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in April 2014 held at the Teluk Meranti Pelalawan Riau Province. Intake of respondents conducted by Quota Sampling. Researchers determined as much as 10% of the respondents 130 nautical tourism visitor numbers bono. People in the District of Teluk Meranti in general are farmers and fishermen, as for the existing fishing activities in these waters is fishing, while farming activities by people not so so much. Location bono, there are marine tourism in Pelalawan Riau Province. Bono is a marine tourism marine tourism located in the district of Teluk Meranti and is usually the center of activities carried out in the Capital District is in the village of Teluk Meranti. Based on the analysis of alternative marine tourism activities can be described bono is still a lack of power as a benchmark in the development of marine tourism including only platforms bono bono, having psychological beaches and great tasik serkab.Keywords: Employment, Contribution Of Marine Tourism Subsector , Kecamatan Teluk Meranti